Negative response of photosynthesis to natural and projected high seawater temperatures estimated by pulse amplitude modulation fluorometry in a temperate coral - Caroselli, Erik; Falini, Giuseppe; Goffredo, Stefano; Dubinsky, Zvy; Levy, Oren (Frontiers in Physiology, 2015)
Balanophyllia europaea is a shallow water solitary zooxanthellate coral, endemic to the Mediterranean Sea. Extensive field studies across a latitudinal temperature gradient highlight detrimental effects of rising temperatures on its growth, demography and skeletal characteristics, suggesting that depression of photosynthesis at high temperatures might cause these negative effects. Here we test this hypothesis by analyzing, by means of pulse amplitude modulation fluorometry, the photosynthetic efficiency of B. europaea specimens exposed in aquaria to the annual range of temperatures experienced in the field (13°C, 18°C, and 28°C), and two extreme temperatures expected for 2100 as a consequence of global warming (29°C and 32°C). The indicators of photosynthetic performance analyzed (maximum and effective quantum yield) showed that maximum efficiency was reached at 20.0-21.6°C, slightly higher than the annual mean temperature in the field (18°C). Photosynthetic efficiency decreased from 20.0°C to 13°C and even more strongly from 21.6°C to 32°C. An unusual form of bleaching was observed, with a maximum zooxanthellae density at 18°C that strongly decreased from 18°C to 32°C. Chlorophyll a concentration per zooxanthellae cell showed an opposite trend as it was minimal at 18°C and increased from 18°C to 32°C. Since the areal chlorophyll concentration is the product of the zooxanthellae density and its cellular content, these trends resulted in a homogeneous chlorophyll concentration per coral surface across temperature treatments. This confirms that B. europaea photosynthesis is progressively depressed at temperatures >21.6°C, supporting previous hypotheses raised by the studies on growth and demography of this species. This study also confirms the threats posed to this species by the ongoing seawater warming.